Gender Differences in Body Image Perception Among College Sports Students - Syifa F. Syihab (Journal of Applied Food and Nutrition, 2020)
Sports students are commonly associated with a healthy body condition and an ideal body shape. The purpose of this study is to examine the differences in body image perceptions between male and female students enrolled in sports studies programs. This study employs a quantitative methodology and a cross-sectional design. The chi-square test was used to analyze the data, with a p-value less than 0.05. Gender affects pupils' self-perceptions of their physical parts, as demonstrated in this study. The results indicate that all body indicators had significant p-values. In this study, most of the students feel satisfied with their body parts, although the number of female students who worried about their appearance was slightly higher compared to male students. Our findings suggest that sports students had a good body image.